Peran Manajemen Kerja dalam Meningkatkan Kinerja Operasional Ritel Modern: Studi Kasus pada Supermarket Fitrinofane - Chinse Alqamar S.F; Pebri Vionauli; Putri Kanayadewi; Nuris Sanida (Jurnal Pengabdian Masyarakat, 2026)
The rapid development of modern retail in Indonesia requires companies to achieve effective and efficient operational performance in order to remain competitive. One of the key factors influencing operational performance is the implementation of proper work management in managing human resources. This study aims to analyze the role of work management in improving the operational performance of modern retail, using Supermarket Fitrinofane as a case study. The research employs a descriptive qualitative approach through a literature review by examining relevant scientific sources related to work management and retail operational performance. The findings indicate that work management practices, including work planning, task allocation, scheduling, supervision, and employee performance evaluation, play a significant role in enhancing employee productivity, operational efficiency, and service quality. Structured work management also helps minimize operational errors and supports better work discipline and coordination among departments. Therefore, work management is a strategic factor in improving the operational performance of Supermarket Fitrinofane and contributes to the sustainability of modern retail businesses in Indonesia.